Effect of preprocessing storage conditions on the carbonyls of oil sardine - and Devadasan, K., Ammu, K. (Fishery Technology, 2021)
Changes in the total as well as major individual carbonyls of oil sardine muscle during storage at room temperature for 24 h and in crushed ice up to 6 days are reported. Carbonyls extracted with hexane were converted to their 2:4 dinitrophenyl hydrazone (DNPH) derivatives and were separated into major classes by column chromatography on celite/magnesia. Individual carbonyls were then identified by capillary gas chromatography of these derivatives. Though absolute values for carbonyls exhibited wide variations depending upon the degree of freshness, the pattern of changes in the carbonyls during storage of fish under different conditions gave an insight into the influence of carbonyls on flavour. The significance of the findings is discussed.